Fungicides and the Grapevine Wood Mycobiome: A Case Study on Tracheomycotic Ascomycete Phaeomoniella chlamydospora Reveals Potential for Two Novel Control Strategies - Del Frari, Giovanni; Gobbi, Alex; Aggerbeck, Marie Rønne; Oliveira, Helena; Hansen, Lars Hestbjerg; Ferreira, Ricardo Boavida (Frontiers in Plant Science, 2019)
Phaeomoniella chlamydospora is a tracheomycotic fungus that colonizes the xylem of grapevines (Vitis vinifera L.), causing wood discoloration, brown wood streaking, gummosis and wood necrosis, which negatively affect the overall health, productivity and lifespan of vines. Current control strategies to prevent or cope with P. chlamydospora infections are frequently ineffective. Moreover, it is unclear how fungicides commonly applied in vineyards against downy and powdery mildew agents affect the wood mycobiome, including wood pathogens such as P. chlamydospora. In this study, we used next-generation sequencing to assess the effects of foliar spray of grapevines with inorganic (copper oxychloride and sulfur), synthetic (penconazol and fosetyl-aluminium) and natural (Blad) fungicides currently used against the downy and powdery mildews. The subjects of our investigation were (i) the resident wood mycobiome, (ii) the early colonization by a consortium of fungal wood endophytes (ACEA1), (iii) the wood colonization success of P. chlamydospora, and (iv) the in planta interaction between P. chlamydospora and ACEA1, under greenhouse conditions, in rooted grapevine cuttings cv Cabernet Sauvignon. The data obtained suggest that the resident mycobiome is affected by different fungicide treatments. In addition, the early colonization success of the endophytes composing ACEA1 varied in response to fungicides, with relative abundances of some taxa being over- or underrepresented when compared with the control. The wood colonization by P. chlamydospora comported significant changes in the mycobiome composition and, in addition, it was greatly affected by the foliar spray with Blad, which decreased the relative abundance of this pathogen 12-fold (4.9%) when compared with the control (60.7%) and other treatments. The presence of the pathogen also decreased considerably when co-inoculated into the plant with ACEA1, reaching relative abundances between 13.9 and 2.0%, depending on the fungicide treatment applied. This study shows that fungicides sprayed to prevent infections of powdery and downy mildews have an effect on non-target fungi that colonize the endosphere of grapevines. We suggest two potential control strategies to fight P. chlamydospora, namely the foliar spray with Blad and the use of ACEA1. Further studies to confirm these results are required.